The Advanced Effectveness And Efficiency of New Testing Analysis - S.Srinivasa rao, Dr; Moulika, G; G, Lalitkumar; Naga Yeshwanth, D (International Journal of Engineering and Technology, 2018)
Testing is the most widely used by the many software companies to develop the product or the project with most reliable. Testing will calculate the efficiency and effectiveness of the product to improve the performance of the project and work with proper way. Based on the testing results the product can be developed more effectively without showing any complications when the product is released. In this paper, the new integrated testing is developed to calculate the testing effectiveness and testing efficiency of the product at the time of releasing and at the time of development of the project. The existing system of this testing shows the early testing which is at the time of the development and the proposed system of the testing shows the late testing of the project i,e after the completion of the project. From the proposed system the cost, penalty, and benefit of a software during its development phase for finding the expected faults and predicted faults to release the product.Â